PELATIHAN DETEKSI TUMBUH KEMBANG ANAK PADA KADER POSYANDU DI DESA KIRING SEMANDING - Mariyatul Qiftiyah; Umu Qonitun; Erna Eka Wijayanti; Nur Cholila (ABDIMASNU: Jurnal Pengabdian kepada Masyarakat, 2021)
The toddler period is a golden period of growth and development that is very important and determines the quality of life for future children. Detection of growth and development during toddlerhood is very important to do to monitor whether there are deviations in the process of child development. Early detection of under-fives growth and development can find irregularities earlier so that the interventions given will be much more effective and efficient. The implementation of Integrated Service Post in Kiring village mostly monitors growth, whereas progress monitoring is only carried out if there is a visit from the community Health centers, due to the limited number of cadres who have attended the DTKB training. The objective of this DTKB training is to improve the cadres' ability to be able to do DTKB properly. The training methods carried out include pre and post-training tests, DTKB counseling, DTKB practice including anthropometric measurements, filling out the MCH booklet on the Card Towards Healthy (KMS) sheet, z-score table, head circumference, interpretation of DTKB assessment results, and counseling on the use of the KIA book. as a medium for health education. The results of the dedication were an increase in the level of knowledge about child development as evidenced by an increase in the pre-post test score of 10-30 points, 14 cadres had attended DTKB training and were able to practice DTKB correctly, the KIA book was not only used to record the results of measuring growth also record the results of development detection and use it as a health education media by cadres